A Study on Livelihood Options among the Tribal in Rayagada District of Odisha (Indian Journal of Extension Education, 2019)
The research study was conducted among randomly selected 120 tribal respondents of Rayagada, district of Odisha to know the priority given by tribal to their livelihood options basing on their practices and experiences. The study revealed that that agriculture as livelihood option was ranked first, followed by government/semi government/private job, horticulture, animal husbandry, fishery, caste-based occupation, NTFP’s collection, agricultural labour and non-agricultural labour, respectively. The mean scores with regard to strength of agriculture, animal husbandry, forestry, fishery and wage labour were estimated as 18.09 ± 0.16, 19.70 ± 0.15, 19.25 ± 0.17, 17.97 ± 0.27 and 19.16 ± 0.16, respectively, with significant difference among them. The mean scores with regard to weakness of agriculture, animal husbandry, forestry, fishery and wage labour were estimated to be 18.89 ± 0.13, 19.25 ±0.17, 16.89 ± 0.13, 17.88 ± 0.22 and 17.98 ± 0.17, respectively, with significant difference among them. The mean scores with regard to opportunity on livelihood options viz. agriculture, animal husbandry, forestry, fishery and wage labour were estimated to as 15.60 ± 0.18, 17.60 ± 0.18, 16.60 ± 0.18, 15.97 ± 0.27, 14.60 ± 0.18, respectively, with significant difference among them. The mean scores with regard to threat were estimated with significant difference among them. The degree of association between annual income and strength was estimated as 0.023. Corresponding values with weakness, opportunity and threat were found to be -0.025, -0.080 and -0.084.